Writing, Calculating and Peer Feedback in a Mathematically-oriented Course for Process Engineers: Raising Motivation and Initiating Processes of Thinking and Learning - Stahlberg, Nadine; Mosler, Stefan; Schlüter, Michael (Journal of Academic Writing, 2016)
Writing assignments can be seen as an important component of learning processes. Especially in the fields of engineering and sciences, writing assignments have the potential to consolidate subject-specific skills and to enhance motivation for solving technical problems. This paper introduces readers to a revised course structure that aims to strengthen motivation and mathematical understanding through written peer feedback based on mathematical exercises with written elements. The assignment was developed for the course Computational Fluid Dynamics in Process Engineering, a mathematically-oriented course for Master students of theoretical mechanical engineering and process engineering. Since the learning content was perceived as complex, students seemed to lack motivation in preparing for the course with the provided exercises. This paper suggests – based on the collected data, consisting of answers to mathematical problems, feedback texts, evaluation results, teachers’ observation, and examination results – that the introduced assignment enhances students’ understanding and has a positive impact on students’ motivation to solve the mathematical exercises.